AB0807 Nailfold capillaroscopy findings are related to the pulmonary function tests values in patients with systemic sclerosis. (23rd January 2014) - Castellví, I.; Sarmiento, M.; Corica, M.E.; Moya-Alvarado, P.; Diaz-Torne, C.; Geli, C.; Laiz, A.; Rodriguez de la Serna, A.; Diaz-Lopez, C.; de Llobet, J.M.; Casademont, J.
Abstract : Objectives: To determine the relation between different pathological capillaroscopic findings and pulmonary function tests in patients with scleroderma. Methods: Retrospective observational study of a cohort of patients with systemic sclerosis (SSc) or early SSc (eSSc) followed in Rheumatology Unit of a University Hospital from 1975 to 2011. Patients who had a nailfold videocapillaroscopy with 120x magnification were selected. The following pathological findings were considered: presence of megacapillaries and/or angiogenesis and loss of capillary density. Capillaroscopic findings were compared with the following values of lung function tests performed in the same year of the capillaroscopy: % predicted forced vital capacity (FVC), DLCO and the FVC/DLCO ratio. The following variables were also included: sex, type of SSc, presence of digital ulcers, interstitial lung disease (ILD), scleroderma renal crisis (SRC) and pulmonary hypertension determined by echocardiogram. Statistical analysis was performed by T Test to compare the capillaroscopic findings and pulmonary function test. Values of p<0.05 were considered statistical significance. Results: Of all patients (n=136), 84 had at least one videocapillaroscopy. We observed that 92, 9% were female, 67% (57/84) had limited SSc, 25, 3% (21/84) ILD, 29, 8% (25/84) DU and 17, 9% (15/84) of patients had PH. We analyzed the capillaroscopics findings with the lung function parameters. We found that patients with loss of capillary density had worse FVC (87% ± 19, 58 vs 101, 12% ± 16, 06, p <0.01) and DLCO (71, 24% ± 21, 37 vs. 85, 9% ± 19, 81, p <0.01). We did not find a relation between alteration in respiratory function tests and the presence of megacapillaries and angiogenesis. Conclusions: Patients with significant loss of capillary density in the nail-fold capillaroscopy showed worst values of FVC and DLCO. Prospective studies are needed to determine if the nail-fold capillaroscopy may be useful to study lung involvement in patients with systemic sclerosis. Disclosure of Interest: None Declared